Perdas de água por escoamento superficial de um solo com diferentes níveis de resíduos vegetais e declividades do terreno - Santa, Cleiton Dalla (2010)
The search for information and technology that can contribute for an adequate management of soil and water utilization has been in an increasing need, as their conservation is of great matter for a sustainable agriculture. The goal of the present work was determining and modelling the water losses through surface runoff, of a soil with different levels of crop residue and declivity, using simulated rainfall. The work was conducted inside an area for experiments of the Departamento de Engenharia Rural da UFSM, in four locations, which had slope of zero, 2.5, 5 e 8%, respectively. The design of the experiment was completely randomized, with three levels of crop residue of oat in the surface (0, 2.5 e 5 Mg ha-1) in three replicates. The parcels of the experiment of 0.5 m2 were delimited using galvanized metal sheets implanted in the soil with a gutter at the bottom, to collect the water of the surface runoff (measuring in 5 minutes intervals). The rainfall intensities of 30, 80 and 120 mm h-1 were applied using a rainfall simulator of multiple and oscillating nozzles, doing two simulations (Rainfall 1 and 2, applied alternately each day) in each slope for each intensity. For each simulated rainfall it was determined the starting time and the runoff rate, besides rain (amount, duration and intensity), initial humidity and soil saturation. For estimating the surface runoff, it was used the modified Smith model. The model parameters were adjusted through multivariate equations. In the Rainfall 1, with intensity of 30 mm h-1 there was no runoff for the zero slope, and for the remaining slopes, the runoff represented 1.0, 8.8 e 11.5% of the amount of rain applied. In the rainfalls with intensity of 80 and 120 mm h-1, the water losses through surface runoff represented about 59 and 53% of the amount of rain applied, respectively. In Rainfall 2, the water losses through surface runoff represented 33, 45 e 73%, of the amount applied, respectively, for the intensities of 30, 80 and 120 mm h-1. The presence of crop residue delays the start of surface runoff and reduces the surface runoff rate, for different rain intensities (30, 80 e 120 mm h-1) and slope steepness (zero, 2.5, 5 and 8%). The multivariate equations generated from the rain characteristics and soil humidity showed good precision in estimating the surface runoff rate and the starting time of the runoff.